2012
DOI: 10.3109/02699052.2012.700082
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based stress reduction (MBSR) improves long-term mental fatigue after stroke or traumatic brain injury

Abstract: The results from the present study show that MBSR may be a promising non-pharmacological treatment for mental fatigue after a stroke or TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
193
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 36 publications
3
193
0
2
Order By: Relevance
“…The most positive effects were seen for ICU-diary interventions in reducing the incidence of PTSD. 69 The authors conclude that more directed interventions and further research are needed before definitive conclusions can be drawn. 53,70 The future Mindfulness meditation is a technique that has been used in other specialities to assist with reducing anxiety, stress and depression, improving coping strategies, reducing mental fatigue, with an overall aim to improve cognitive function and overall quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most positive effects were seen for ICU-diary interventions in reducing the incidence of PTSD. 69 The authors conclude that more directed interventions and further research are needed before definitive conclusions can be drawn. 53,70 The future Mindfulness meditation is a technique that has been used in other specialities to assist with reducing anxiety, stress and depression, improving coping strategies, reducing mental fatigue, with an overall aim to improve cognitive function and overall quality of life.…”
mentioning
confidence: 99%
“…Authors found that there was a significant improvement in mental fatigue, anxiety and depression self-assessment scores and word fluency and information processing speed following an 8-week programme using a mindfulness-based stress reduction (MBSR) approach. 69 Potential mechanisms are thought to be mediated by structural changes in the left prefrontal cortex and associated with changes in emotion regulation that can impact on cognition, emotion and behaviour. 71 …”
mentioning
confidence: 99%
“…The data are taken from previously published studies and also from unpublished studies [27,[30][31][32][33]. In these studies we have used the same assessments with rating scales and cognitive tests, and in this study, we have only used the baseline data taken from these studies.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the yoga intervention group had significant improvements in HRQOL, and participants reported high satisfaction ratings indicating that yoga is potentially feasible for individuals with brain injuries. Other studies examined the effects of mindfulness-based stress reduction (MBSR) for individuals after TBI [25,26], and MBSR programs contain a Hatha yoga element but are not designed to be yoga interventions [27]. There is however more yogaspecific research available regarding other clinical populations (non-TBI).…”
Section: Introductionmentioning
confidence: 99%